THE EFFECT OF GIVING PAPAYA (CARICA PAPAYA L) ON INCREASING THE VOLUME OF BREAST MILK PRODUCTION BREASTFEEDING MOTHERS IN NGEMBAK VILAGE, PURWODADI DISTRICT - Wiwit Sugiarti; Yuwanti; Wahyu Utami Ekasari (The Shine Cahaya Dunia Kebidanan, 2024)
Background: One of the problems that often occurs in the breastfeeding process is the lack of smooth breast milk production, this makes most mothers choose to give their babies formula milk. To overcome this problem, papaya can be used as a breast milk booster because it contains lactagogum which can affect breast milk production. WHO and UNICEF noted that exclusive breastfeeding coverage in 2019 reached 41%. Meanwhile, in Ngembak Village itself, exclusive breastfeeding coverage is still relatively low, namely 66.67% in 2023. The aim of this research is to find out the effect of giving papaya on increasing the volume of breast milk production among breastfeeding mothers in Ngembak Village, Purwodadi District. Method: This study is a quantitative study using a pre-experimental design with a one-group pre-test post-test design. With a sampling technique of purposive sampling. The sample in the study was 35 breastfeeding mothers and the analysis test used was the Independent T-test. Results: The results of the study show that there is an effect of giving papaya on increasing the volume of breast milk production in breastfeeding mothers with a p-value of 0.000. Conclusion: Based on the results of this research, it can be concluded that there is an effect of giving papaya on increasing the volume of breast milk production in breastfeeding mothers in Ngembak Village, Purwodadi District.